The Impact of Elevated Mean Arterial Pressure on Mortality in Spontaneous Subarachnoid Hemorrhage - Achmad Firdaus Sani; Taurus Laisari; Muh. Wildan Yahya; Vita Kusuma Rahmawati; Faishol Hamdani; Dedy Kurniawan; Sita Setyowatie (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: Elevated MAP is associated with increased in-hospital mortality in SAH patients High MAP increases the risk of rebleeding, cerebral edema, and vasospasm MAP, age, infection, and hydrocephalus are independent predictors of mortality ABSTRACT Introduction: Subarachnoid hemorrhage (SAH) remains a critical neurological emergency with high mortality and morbidity. Mean arterial pressure (MAP) plays an importance role in cerebral perfusion and hemodynamic stability in SAH patients. However, excessive MAP elevation potentially worsening clinical outcomes. This study investigates the impact of elevated MAP on in-hospital mortality among SAH patients. Objective: This study investigates the impact of elevated MAP on in-hospital mortality among SAH patients. Method: A retrospective cross-sectional study was conducted using medical records of SAH patients admitted to Dr. Soetomo Academic Medical Center Hospital from 2013 to 2021. A total of 360 patients met the inclusion criteria. MAP was calculated upon admission and categorized as ≥125 mmHg or <125 mmHg. The primary outcome was in-hospital mortality. Logistic regression analysis was performed to assess the association between MAP and mortality while adjusting for confounders. Result: Among 360 SAH patients, 44.8% did not survive hospitalization. The mean age was 54 years, with an initial mean MAP of 117.45±21.6 mmHg. Bivariate analysis showed that MAP ≥125 mmHg significantly increased mortality risk (OR = 1.93; 95% CI: 1.24–2.98; p = 0.002). Multivariate logistic regression identified MAP ≥125 mmHg as an independent predictor of mortality (Adjusted OR = 1.795; p = 0.012), alongside age (Adjusted OR = 2.043; p = 0.004), infection (Adjusted OR = 2.442; p = 0.001), and hydrocephalus (Adjusted OR = 2.174; p = 0.003). Conclusion: Elevated MAP (≥125 mmHg) is significantly associated with increased in-hospital mortality in SAH patients. These findings highlight the importance of early hemodynamic management in SAH to improve patient survival.